2009
DOI: 10.2187/bss.23.23
|View full text |Cite
|
Sign up to set email alerts
|

The Transcript Level of Katanin Gene is Increased Transiently in Response to Changes in Gravitational Conditions in Azuki Bean Epicotyls

Abstract: Development of a short and thick body by re orie ntation of cor tical microtubule s is required for the resistance of plants to the gravitational force. Katanin has microtubules e ve r i n g a c t i v i t y a n d i s i nvo l ve d i n t h e reorientation of cortical microtubules. Here, we investigated the effects of hypergravity produced by centrifugation on the expression of VaKTN1 gene encoding katanin. Hypergravity at 300 G increased the transcript level within 15 min, and the level reached maximum at 45 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…19,20 In our recent study, we found that gadolinium ions decreased the alignment angle of epidermal cell files and that of cortical region of azuki bean epicotyls, cells with transverse cortical microtubules were predominant at 1 g. Hypergravity induces reorientation of cortical microtubules from transverse to longitudinal directions. 9 In addition, hypergravity increased transiently the expression of γ-tubulin and katanin genes, 10,11 which are assumed to be responsible for reorientation of cortical microtubules. 12 These results suggest that cortical microtubules are involved in gravity resistance.…”
Section: Involvement Of Mechanoreceptors In Gravity Resistancementioning
confidence: 99%
“…19,20 In our recent study, we found that gadolinium ions decreased the alignment angle of epidermal cell files and that of cortical region of azuki bean epicotyls, cells with transverse cortical microtubules were predominant at 1 g. Hypergravity induces reorientation of cortical microtubules from transverse to longitudinal directions. 9 In addition, hypergravity increased transiently the expression of γ-tubulin and katanin genes, 10,11 which are assumed to be responsible for reorientation of cortical microtubules. 12 These results suggest that cortical microtubules are involved in gravity resistance.…”
Section: Involvement Of Mechanoreceptors In Gravity Resistancementioning
confidence: 99%
“…When expression profiles of katanin gene were compared with those of g-tubulin complex genes, the peak of expression of katanin gene was delayed by 1.0 to 1.5 h. The delay of the peak of expression of katanin gene was also observed during hypergravity-induced reorientation of cortical microtubules from transverse to longitudinal directions. 10,11 These results indicate that microtubule-severing activities are increased by ethylene and hypergravity via upregulation of katanin gene, resulting in the stimulation of separation of the newly synthesized microtubule branch via g-tubulin complex (Fig. 1).…”
Section: Acknowledgementsmentioning
confidence: 84%
“…2 By removal of the hypergravity stimulus, the transcript levels of g-tubulin complex and katanin genes were increased transiently. 10,11 These results indicate the transcription of g-tubulin complex and katanin genes is stimulated transiently during reorientation of cortical microtubules, irrespective of the direction of reorientation of the microtubules.…”
mentioning
confidence: 88%
“…As the final step of gravity resistance, plants developed a short and thick body and increased cell wall rigidity to resist the gravitational force. The modification of body shape was brought about by the rapid reorientation of cortical microtubules that was caused by the action of microtubule-associated proteins in response to the magnitude of the gravitational force (Soga et al, , 2009. The regulation of the cell wall rigidity was brought about by modification of the metabolisms of antigravitational cell wall polysaccharides (Hoson and Soga, 2003;Nakano et al, 2007).…”
Section: Introductionmentioning
confidence: 99%